2008
DOI: 10.1002/art.23300
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system vasculitis with prominent leptomeningeal enhancement: A subset with a benign outcome

Abstract: Objective. Primary central nervous system vasculitis (PCNSV) is an uncommon condition that affects the brain and spinal cord. This study was undertaken to evaluate the clinical features and outcomes among patients with PCNSV who presented with prominent gadolinium meningeal enhancement on magnetic resonance imaging (MRI).Methods. Through retrospective review using the Mayo Clinic medical records linkage system, we identified 101 consecutive patients with PCNSV based on brain biopsy or conventional angiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 24 publications
(39 reference statements)
1
56
0
Order By: Relevance
“…However, isolated small-sized vessel PCNSV involves a subgroup of patients in whom DSA findings (and a fortiori 3D-TOF-MRA) are also mostly negative, and only biopsy can show vascular involvement in these patients. 9,[20][21][22] In our first description of the French cohort, as well as in another large study by Salvarani et al, 23 twothirds of the patients with biopsy-proved PCNSV had negative DSA findings. 9 In the present study, 6 of our 7 patients with isolated small-sized vessel vasculitis demonstrated by biopsy had normal 3D-TOF-MRA and DSA findings.…”
mentioning
confidence: 57%
“…However, isolated small-sized vessel PCNSV involves a subgroup of patients in whom DSA findings (and a fortiori 3D-TOF-MRA) are also mostly negative, and only biopsy can show vascular involvement in these patients. 9,[20][21][22] In our first description of the French cohort, as well as in another large study by Salvarani et al, 23 twothirds of the patients with biopsy-proved PCNSV had negative DSA findings. 9 In the present study, 6 of our 7 patients with isolated small-sized vessel vasculitis demonstrated by biopsy had normal 3D-TOF-MRA and DSA findings.…”
mentioning
confidence: 57%
“…Since the first histological description in 1922 [5] about 500 cases have been published worldwide [42]. One of the most relevant studies is the recent series of 101 patients from the Mayo Clinic [28,[35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically and pathophysiologically it makes sense that patients with microangiopathy have a worse outcome. Further interpretations about outcome concluded on the base of the different subgroups of Mayo Clinic's cohort should be regarded considering potential limitations and bias [28,[35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations